2012
DOI: 10.1007/s11214-012-9949-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Belt Storm Probes—Observatory and Environments

Abstract: The National Aeronautics and Space Administration's (NASA's) Radiation Belt Storm Probe (RBSP) is an Earth-orbiting mission that launched August 30, 2012, and is the latest science mission in NASA's Living with a Star Program. The RBSP mission will investigate, characterize and understand the physical dynamics of the radiation belts, as well as the influence of the Sun on the Earth's environment, by measuring particles, electric and magnetic fields and waves that comprise geospace. The mission is composed of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…These times of negative charging in sunlight present a unique situation. Extreme care was taken on the Van Allen Probes satellites to ensure a conducting spacecraft, and previous studies have shown, based on model results, that significant negative spacecraft charging should not occur in sunlight on a conducting spacecraft [Davis et al, 2012;Kirby et al, 2014]. In particular, we see from Figure 3 in the postmidnight sector at L > 4, there are a large number of negative spacecraft charging events, where hot electrons begin to gradient curvature drift eastward as they enter from the plasma sheet.…”
Section: Observations From Efwmentioning
confidence: 76%
“…These times of negative charging in sunlight present a unique situation. Extreme care was taken on the Van Allen Probes satellites to ensure a conducting spacecraft, and previous studies have shown, based on model results, that significant negative spacecraft charging should not occur in sunlight on a conducting spacecraft [Davis et al, 2012;Kirby et al, 2014]. In particular, we see from Figure 3 in the postmidnight sector at L > 4, there are a large number of negative spacecraft charging events, where hot electrons begin to gradient curvature drift eastward as they enter from the plasma sheet.…”
Section: Observations From Efwmentioning
confidence: 76%
“…Since the analysis in this paper is specifically aimed at low‐energy electrons, it is critical that surface charging on the spacecraft is low, that the effects from photoelectrons and secondaries are minimized, and that penetrating background radiation is mostly negligible, in order that the instrumentation reports fluxes based on the conditions in orbit. A large effort was made in the design of the satellite platform and in the choice of materials used in construction, in order to minimize the buildup of surface charge on the spacecraft, to prevent localized potential wells, and to inhibit the effects of penetrating background radiation [ Kirby et al , ]. This effort was supplemented by prelaunch environmental tests that demonstrated that the platform would have a very low susceptibility to surface charging once on orbit [ Kirby et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…A large effort was made in the design of the satellite platform and in the choice of materials used in construction, in order to minimize the buildup of surface charge on the spacecraft, to prevent localized potential wells, and to inhibit the effects of penetrating background radiation [ Kirby et al , ]. This effort was supplemented by prelaunch environmental tests that demonstrated that the platform would have a very low susceptibility to surface charging once on orbit [ Kirby et al , ]. The level of spacecraft charging can be estimated from the Electric Fields and Waves (EFW) instrument on board Van Allen Probes [ Wygant et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in South Korea, the antenna receives space weather data approximately 20% of the time. The data are transmitted to the ground via S‐band using 8 W solid‐state power amplifier transmitters (Kirby et al, ).…”
Section: Receipt Of Near‐real‐time Space Weather Data From the Vapsmentioning
confidence: 99%